Improving Learning Outcomes of Football Passing with the Triangle Goal Game Method in Class VII A of SMP N 42 Semarang - Arif, Muhammad; Azizah, Nurul; Akhiruyanto, Andry (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
The background of the research is that there are still many VII D students at SMPN 42 Semarang who have learning outcomes for football passing below the success criteria. This research aims to determine the effect of the triangle goal game method on the passing learning outcomes of class VII D students at SMPN 42 Semarang. The type of research used is classroom action research. The subjects in this research were students in class VII D of SMP Negeri 42 Semarang with a total of 32 students. The research instrument uses an assessment rubric. The data analysis technique uses comparative descriptives, namely comparing pre-cycle, cycle I, cycle II. The research results showed that the learning outcomes in cycle I were 17 students or 50% of students who had achieved the success criteria and 17 students or 50% of students had not achieved the success criteria. The average student score in cycle I was 76.35. In cycle II, there were 30 students or 89% of students who had achieved the success criteria and 4 students or 11% of students had not reached the criteria. The average student score in cycle II was 82.71. The conclusion of the research is that the percentage of students' success criteria from the pre-cycle was 35% which increased in cycle I to 50% who achieved the criteria and experienced an increase again in cycle II, namely 89% of students achieved the success criteria so that the success target was achieved.